Exercise and cognitive function: a hypothesis for the association of type II diabetes mellitus and Alzheimer's disease from an evolutionary perspective - Brito, Gilberto N. O. (2009)
Fundação Oswaldo Cruz. Instituto Fernandes Figueira. Departamento de Pediatria. Setor de Neurociências. Rio de Janeiro, RJ, Brasil. / Universidade Federal Fluminense. Instituto de Saúde daComunidade. Departamento de Psiquiatria e Saúde Mental. Niterói, RJ, Brasil.